Effectiveness of Physiotherapy Interventions for Hand Dysfunction in Rheumatoid Arthritis: A Systematic Review of Randomized Controlled Trials - Jaya, Pathak; Deepak, Anap; Nilesh, Dond (VIMS JOURNAL OF PHYSICAL THERAPY, 2025)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory polyarthritis that commonly affects the hands and wrists, leading to pain, stiffness, and functional impairment. Hand exercises are often prescribed as part of physiotherapy management to enhance mobility, strength, and overall hand function. Various physiotherapeutic approaches have been employed to address hand dysfunction in individuals with RA. In the present study, we conducted a systematic review of randomized controlled trials (RCTs) evaluating the effectiveness of physiotherapy interventions aimed at improving hand function in patients with rheumatoid arthritis. Method: We conducted a comprehensive literature search in the Medline, CINAHL, Cochrane Library, PubMed, and Google Scholar databases using the keywords "physiotherapy intervention for hand dysfunction" and "rheumatoid arthritis." The search covered studies published between January 2015 and January 2025. Only randomized controlled trials (RCTs) that evaluated physiotherapy interventions for improving hand function in patients with rheumatoid arthritis were included in this review. Result: This systematic review analyzed data from 10 reliable studies focusing on physiotherapy interventions for hand dysfunction in patients with rheumatoid arthritis (RA). The evidence indicates that strengthening exercises, use of theraputty, and proprioceptive training are effective in reducing pain and enhancing hand function. Among the interventions studied, the CareHand program and Yijinjing exercise emerged as the most effective for improving overall hand function and dexterity in individuals with rheumatic hand involvement. Conclusion: The findings of this review support the effectiveness of physiotherapeutic interventions in managing hand dysfunction associated with rheumatoid arthritis. These interventions contribute to reducing pain and morning stiffness, while improving hand function and quality of life Keywords: Rheumatoid Arthritis, Hand Dysfunction, Physiotherapy